Volumetric 18F‐FDG‐PET parameters as predictors of locoregional failure in low‐risk HPV‐related oropharyngeal cancer after definitive chemoradiation therapy. Issue 2 (12th December 2018) - Chotchutipan, Thong; Rosen, Benjamin S.; Hawkins, Peter G.; Lee, Jae Y.; Saripalli, Anjali L.; Thakkar, Dharmesh; Eisbruch, Avraham; El Naqa, Issam; Mierzwa, Michelle L.
Abstract: Background: We sought to investigate the prognostic value of volumetric positron emission tomography (PET) parameters in patients with human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (OPSCC) and a ≤10 pack‐year smoking history treated with chemoradiation. Methods: A total of 142 patients were included. Maximum standardized uptake value, metabolic tumor volume, and total lesion glycolysis (TLG) of the primary tumor, involved regional lymph nodes, and total lesion were calculated. Cox proportional hazard modeling was used to evaluate associations of clinical and PET parameters with locoregional failure‐free survival (LRFFS), distant metastasis‐free survival (DMFS), and overall survival (OS). Results: On univariate analysis, volumetric PET parameters were significantly associated with all endpoints, and 8th edition American Joint Committee on Cancer/Union Internationale Contre le Cancer staging was significantly associated with DMFS and OS. On multivariate analysis, total lesion TLG was significantly associated with LRFFS, while staging was most significantly prognostic for DMFS and OS. Conclusion: Volumetric PET parameters are uniquely prognostic of LRFFS in low‐risk HPV‐related OPSCC and may be useful for directing de‐intensification strategies.